Cardiac computed tomography for cardiac masses: a necessity or a luxury? - Imane Joudar; Siham Nasri; Imane Kamaoui; Imane Skiker (Journal of International Medical Research)
Cardiac masses present a considerable diagnostic challenge because of their diverse causes and potential clinical implications. Traditional imaging methods, such as transthoracic echocardiography and transesophageal echocardiography, are crucial for initial assessments owing to their accessibility, but they have a major limitation represented by inter-operator variability. Therefore, cardiac computed tomography (CT) has become an indispensable adjunct, providing detailed anatomical information and tissue characterization. This review examines the prevalence, categorization and diagnostic benefits of cardiac CT in the evaluation of cardiac masses. The high-resolution imaging and multiplanar features of cardiac CT allow in-depth assessment of the structure, location and enhancement patterns of masses, helping to distinguish benign from malignant masses and guide clinical decision-making. Specific imaging features of benign and malignant tumors, as well as non-neoplastic masses, are discussed, highlighting the role of CT in overall cardiac assessment. This article highlights the importance of CT in surgical preparation, risk assessment and ongoing monitoring, and highlights its effect on improving patients’ outcomes. With continued advances in CT technology, the integration of this modality into routine clinical practice should improve the accuracy of diagnosis and management of cardiac masses, strengthening the essential role of cardiac CT as a vital component of contemporary cardiovascular imaging.